Eventos adversos frecuentes en una institución prestadora de salud tercer nivel de complejidad en el período 2016 - 2017 (2021)
To determine the most frequent adverse events in a Third Level Complexity Healthcare Institution during the years 2016-2017 and propose strategies to prevent or minimize these events. Materials and method: Quantitative, descriptive, retrospective research, where the AE information registered in the database of an IPS of Montería, years 2016 and 2017, was analyzed. Results: During the years 2016 and 2017 in a Health Service Provider Institution of Montería 118 and 104 adverse events were registered respectively, with the following behavior: in 2016 the infections caused by health care were more frequent 42.55% , followed by leakage of patients 24.46%, no sentinel events were reported, the services with the highest number of adverse events were delivery room 24.47%, followed by adult emergency 22.34%. On the other hand, in 2017, the most frequent AE were those related to resource management or organizational management 28.57% followed by patient falls 18.25%, 32% of the events were sentinels caused mainly by the management of resources or with organizational management, and the services where AE were most presented were Pensioner B 24.60%, Internal Medicine 22.22% and Adult Emergencies 17.46%. On the other hand, the months where the greatest number of adverse events were registered coincide in both years September 19.15% and 17.46%, and October 14.89% and 26.98% respectively, in both years, the most affected people were between the age range of 29 -59; 38.3% and 36.5% respectively, and in the two years there was a predominance of adverse events in women than in men with 63.83% and 59.52% respectively